Construct validity of the IWP Multi-Affect Indicator scale in Romanian work environment - Butucescu, Andreea; Zanfirescu, Șerban-Andrei; Iliescu, Dragoș (Psihologia Resurselor Umane, 2019)
The purpose of this study was to investigate the construct validity of the IWP Multi-Affect Indicator scale. A questionnaire was administered to an occupationally heterogeneous sample of 341 employees. Confirmatory factor analysis (CFA) was used to determine the factor validity of the questionnaire. We employed network analysis as a novel approach to elucidate differential relationships involving the IWP Multi-Affect Indicator’s four-factor structure. CFA results revealed satisfactory model fit, ,best represented by a 4-factor model for the Romanian sample, while network analysis confirmed the relationships between items and factors. We have concluded that this questionnaire is suitable to measure differentiated core affects among Romanian employees.